Authentication of meat species in sucuk by multiplex PCR - Ilhak, Osman Irfan; Güran, Hüsnü Şahan (Istanbul University, 2015)
The identification of meat species used in meat products is important by reason of economic considerations, religious factors, verification of label, and prevention of unfair-market competition. In this paper, multiplex PCR method was experienced for routine detection of equine (horse and donkey), poultry (chicken and turkey), pig and cattle meat in sucuk (sausage). The primers used for these animals generated specific fragments, and they did not show cross reactions with the DNA from the other genus of animal. After multiplex PCR was successfully optimized, a field study was carried out to investigate the presence of horse, donkey, chicken, turkey and pig meat in 50 sucuks (30 beef and 20 beef + poultry) collected from markets. The result of the field study indicated that 23.3% of 30 beef sucuk samples were containing poultry meat. None of the 50 sucuk samples was containing pig meat, but one (2%) of the samples generated equine fragment. The present study showed that the multiplex PCR method can be used for routine analysis of meat species identification, verification and control of label information of meat products.
Keywords: Multiplex PCR; Species identification; Sucuk